COMPARISON OF SPECTRA AND MEAN GLANDULAR DOSE WITH TUBE VOLTAGES USED IN DIGITAL BREAST TOMOSYNTHESIS FROM SIMULATED, METROLOGICAL AND CLINICAL CASES. Issue 3 (16th December 2020) - da Silveira Gatto, Leandro Barbosa; Braz, Delson; Pacifico, Leonardo; Travassos, Paulo; Magalhaes, Luis Alexandre Goncalves
Abstract: Digital breast tomosynthesis (DBT) is a screening and diagnostic modality that acquires images of a breast at multiple angles during a short scan. The Selenia Dimensions (Hologic, Bedford, Mass) DBT system can perform both full-field digital mammography and DBT. The system acquires 25 projections over a 15° angular range (from −7.5° to +7.5°). X-ray spectroscopy is generally linked with a high-resolution semiconductor detector through a correction to its energy response function. The energy spectrum describes the radiation field, in which several quality parameters can be extracted, such as the effective energy, half-value layer and exposure. X-ray spectroscopy is usually performed with solid-state semiconductor detectors. Radiation dose is a concern in mammography, as the current protocols recommend that medical physicians evaluate mean glandular dose (MGD) as a part of service quality control. Studies are needed for radiation dose optimization from tomosynthesis patients. The COMET metrological X-ray tube, considered as with a constant potential and cooled, has proved to be a crucial tool in order to obtain the high energy resolution for low-energy radiographs in mammography. The Monte Carlo method, through Monte Carlo N-Particle eXtended (MCNPX), was proven to be an essential tool for image formation and posterior analysis of the deposited dose from breast simulators and radiographic contrast evaluation, for several anode/filter combinations. The purpose of this work was to assess the MGD and spectra in slabs of polymethyl methacrylate (PMMA) and breast equivalent thicknesses using four experiments with a Hologic Selenia Dimensions mammography X-ray tube with multimeter, a spectrometer (only for spectra, in this case), a metrological X-ray tube with a multimeter, and the MCNPX code. References indicate that the real conditions for a mammography X-ray tube that conducts tomosynthesis include tube voltages of 26, 29, 30 and 33 kVp. Taking into account several thicknesses of PMMA, both the MGD and spectral results were in accordance with the references. Most of the spectra were in accordance with the references, showing that the resources used in the experiments can evaluate the energy level received by a patient. The MGD values were lower than those in the references from 30 to 50 mm PMMA, and the data can be used for improvements in the detectors used in the Laboratory of Metrology in the State of Rio de Janeiro University, Brazil. Additionally, in the future, optimization of image quality can be performed for both semiconductors and mammography X-ray equipment.